(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
This paper examines different supervisory approaches. The discussion has been limited to two approaches, namely the master/apprentice approach and the laissez-faire approach. This is followed by a documentation of the typical problems that arise between supervisors and research students. These problems include: conflicting or unrealistic expectations of each other, poor feedback, tensions or conflicting perspectives from within the supervision panel, supervisor’s lack of knowledge and experience in research and supervision. Each problem is followed by a discussion of possible conflict resolution mechanisms.